A Rapid and Sensitive LC-MS/MS Assay for the Determination of Saxagliptin and its Active Metabolite 5-hydroxy Saxagliptin in Human Plasma and its Application to a Pharmacokinetic Study - Batta, N.; Pilli, N. R.; Derangula, V. R.; Vurimindi, H. B.; Damaramadugu, R.; Yejella, R. P. (Drug Research, 2015)
The authors proposed a simple, rapid and sensitive liquid chromatography-tandem mass spectrometric (LC-MS/MS) assay method for the simultaneous determination of saxagliptin and its active metabolite 5-hydroxy saxagliptin in human plasma. The developed method was fully validated as per the US FDA guidelines. The method utilized stable labeled isotopes saxagliptin-15 N d2 (IS1) and 5-hydroxy saxagliptin-15 N-d2 (IS2) as internal standards for the quantification of saxagliptin and 5-hydroxy saxagliptin, respectively. Analytes and the internal standards were extracted from human plasma by a single step solid-phase extraction technique without drying, evaporation and reconstitution steps. The optimized mobile phase was composed of 0.1% acetic acid in 5 mM ammonium acetate and acetonitrile (30:70, v/v) and delivered at a flow rate of 0.85 mL/min. The method exhibits the linear calibration range of 0.05–100 ng/mL for both the analytes. The precision and accuracy results for both the analytes were well within the acceptance limits. The different stability experiments conducted in aqueous samples and in matrix samples are meeting the acceptance criteria. The chromatographic run time was set at 1.8 min; hence more than 400 samples can be analyzed in a single day.
Keywords: saxagliptin and 5-hydroxy saxagliptin; human plasma; liquid chromatography-tandem mass spectrometry (LC-MS/MS); method validation; pharmacokinetics